A new species of bright-eyed treefrog (Mantellidae) from Madagascar, with comments on call evolution and patterns of syntopy in the Boophis ankaratra complex - Hutter, Carl R.; Lambert, Shea M.; Cobb, Kerry A.; Andriampenomanana, Zo Faniry; Vences, Miguel (Zootaxa, 2015)
We describe a new species of Boophis treefrog from Ranomafana National Park in the southern central east of Madagascar. This region has remarkably high anuran diversity, and along with neighbouring sites, hosts more than 35 Boophis species. Boophis boppa sp. nov. is part of the B. ankaratra sub-clade (herein named the B. ankaratra complex), previously identified within the monophyletic B. albipunctatus species group. It occurs sympatrically with two other species of the complex (B. ankaratra and B. schuboeae). Morphological differentiation of species within the B. ankaratra clade remains elusive, but species are well characterized by distinct advertisement calls, with B. boppa having the longest note duration and inter-note intervals when compared to closely related species. Furthermore, it has moderate differentiation in mitochondrial DNA, with pairwise distances of 1.9–3.7% to all other species in sequences of the mitochondrial 16S rRNA marker. Additional evidence is given by the lack of haplotype sharing with related species for the nuclear exon DNAH-3. All examples of syntopic occurrence in this complex involve species with strongly different advertisement calls, while allopatric species have more similar calls. Such a pattern might result from adaptive call co-evolution but could also be the result of non-adaptive processes. Thorough clarification of the systematics of the B. ankaratra sub-clade is required, and we outline future directions for both bioacoustic and genetic research.